Evaluating the impact of cell-penetrating motif position on the cellular uptake of magnetite nanoparticles - Salgado, Laura; Cifuentes-Delgado, Paula C.; Orozco, Juan Camilo; Muñoz-Camargo, Carolina; Reyes, Luis H.; Quezada, Valentina; Cruz, Juan C. (Frontiers in Bioengineering and Biotechnology, 2024)
Cell-penetrating peptides (CPPs) have been employed to enhance the cellular uptake and intracellular delivery of various nanocarriers. Among them, nanoparticles (NPs) have been used as suitable vehicles for delivering different bioactive molecules in the treatment of a diverse range of diseases. Given the pivotal role of the conjugation method of CPPs, this study aims to evaluate the impact of the position of a cell-penetrating motif (LFVCR) on the biocompatibility, cellular uptake, and endosomal escape of magnetite NPs. The designed peptide's physicochemical properties suggest they are well-suited for efficient cell penetration with minimal cytotoxicity. The resulting designed nanoconjugates were characterized using Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), dynamic light scattering (DLS), and transmission electron microscopy (TEM). The results indicate that motif position significantly impacts the cellular uptake and endosomal escape of the designed nanobioconjugates. Key findings suggest that motif exposure enhances endocytosis-mediated cell internalization and improves endosomal escape efficiency. These results were compared with nanobioconjugates displaying previously reported CPPs. The selected nanobioconjugate demonstrated superior performance in endosomal escape and comparable cell uptake to the reference nanobioconjugates. These results, along with the nanobioconjugate's physicochemical characteristics and high biocompatibility, position the nanocarrier as a suitable candidate for delivering diverse bioactive molecules.